Cerebral magnetic resonance imaging findings in stable cirrhotic patients without clinical signs of hepatic encephalopathy - Yücel ÜSTÜNDAĞ; Süreyya BOYACI; İhsan ÜSTÜN; Fikri AK; Tankut KÖSEOĞLU; Erdal ESKİOĞLU (Turkish Journal of Gastroenterology, 2019)
-